Model Pengembangan Optimalisasi Pelayanan Publik Melalui Peningkatan Pemanfaatan Digitalisasi dan Sistem Informasi di Pemerintah Daerah Kabupaten Bekasi - Cahya Nur Hidayat; Rd. Tati Kurniati; Ferry Mardihardjo D (Balitbangda Kabupaten Bekasi, 2024)
Abstract - Public services in government are things that must be implemented, by utilizing information technology to improve the performance of government administration will be more effective and efficient, as well as providing convenience in governance and public services. The purpose of this research is the existence of a study book on the Development Model of Public Service Optimization Through Increasing the Utilization of Digitalization and Information Systems in the Bekasi Regency Regional Government, while the method used is Mixed Method Research (MMR). Mixed Method Research or joint research is a stage of data collection, data analysis, with a combination of sequential methods, namely quantitative and qualitative methods or vice versa. It is hoped that this study can integrate all SKPDs that have public services using the MPP application. Increasing the Utilization of Digitalization and Information Systems within the Bekasi Regency Government is to increase.